PERANCANGAN KONTROL NIRKABEL PERANGKAT ELEKTRONIK MENGGUNAKAN KONSEP INTERNET OF THING (IoT) - mayda waruni; aswadul fitri (Lembaga Penelitian Universitas Balikpapan, 2018)
Abstract—The technology that is developing at this time demands various developments or the latest innovations, one of them is an embedded system that is connected to the internet network or known as internet of things (IoT). IoT can be used to control various types of electronic devices (embedded systems) anywhere and anytime as long as they are connected to the network. This study will discuss how to design wireless electronic devices that can be controlled remotely with the IoT concept, this design is expected to help people control electronic devices at home..